2018
DOI: 10.1002/stc.2302
|View full text |Cite
|
Sign up to set email alerts
|

Semiactive conceptual fuzzy control of magnetorheological dampers in an irregular base-isolated benchmark building optimized by multi-objective genetic algorithm

Abstract: Summary Seismic base isolations are well‐established passive control systems, used for reducing structural responses and preventing interior sensitive equipment and nonstructural elements from damaging. However, in a base‐isolated structure under near‐fault earthquakes, isolated layers sustain large displacements that might not be allowable. Further, any passive limitation in these displacements amplifies vibration transmissions to the superstructure. Smart hybrid base isolations using magnetorheological (MR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Moreover, a multi-genetic algorithm was applied to the fuzzy controller to optimize the controller's performance. This resulted in similar findings to those of Ndemanou and Nbendjo, where fuzzy controllers performed better than other controllers [186].…”
Section: Semi-active Controllers For Mr Damperssupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, a multi-genetic algorithm was applied to the fuzzy controller to optimize the controller's performance. This resulted in similar findings to those of Ndemanou and Nbendjo, where fuzzy controllers performed better than other controllers [186].…”
Section: Semi-active Controllers For Mr Damperssupporting
confidence: 84%
“…8 Mousavi (2020) [197] Fuzzy logic controller Use of wavelet networks and fuzzy logic controllers to copy the inverse dynamics of MR dampers and nonlinear isolators. (2017) [186] Fuzzy logic controller Improving a fuzzy control system with a smart multi-objective fuzzy-genetic controller produced controls that were more effective than others.…”
mentioning
confidence: 99%
“…They have concluded that the MVO is more effective in reducing the building responses than other Meta-heuristic Algorithms. Mehrkian et al 2 proposed a conceptual Multi-Objective Fuzzy-Genetic Control for vibration control of base-isolated 8storey irregular building subjected to seismic excitations. This controller combines FLC optimized with Multiobjective GA method of Non-dominated Sorting Genetic Algorithm-II (NSGA-II).…”
Section: Fuzzy Logic Controlmentioning
confidence: 99%
“…see [2,3]). Structural control applications can be classified as passive, semi-active, active, and hybrid control systems [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%